2013
DOI: 10.4025/actascibiolsci.v35i2.15359
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of larvae of the hybrid surubim Pseudoplatystoma sp. under two conditions of food management

Abstract: ABSTRACT. We evaluated the growth and diet composition of hybrid surubim larvae (Pseudoplatystoma corruscans x P. reticulatum) produced in two fish farming by using different systems of feeding with natural plankton: M I, larvae are transferred to fertilized fish pond for being freely fed with natural plankton; M II, larvae are remained inside laboratory in glass fiber boxes and plankton are gathered with a plankton net and offered in a controlled way. It was collected 10 individuals daily during the feeding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This behavior is considered an adaptive strategy of some zooplankton organisms to prevent predation. da Silva, et al [5]) observed that in the stomach contents of hybrid catfish larvae (Pseudoplatystoma corruscans x P. reticulatum) kept in a previously fertilized pond, the food item Macrothrix sp. (0.44%) was the least consumed live prey, attributed mainly to them being organisms typical of benthic regions that may be captured only by larvae that exhibit this benthic behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is considered an adaptive strategy of some zooplankton organisms to prevent predation. da Silva, et al [5]) observed that in the stomach contents of hybrid catfish larvae (Pseudoplatystoma corruscans x P. reticulatum) kept in a previously fertilized pond, the food item Macrothrix sp. (0.44%) was the least consumed live prey, attributed mainly to them being organisms typical of benthic regions that may be captured only by larvae that exhibit this benthic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The bryconids' life cycle is characterized by a fast embryonic stage (12-14 h to 26-28 • C); the larvae begin the exogenous feeding between 22 and 24 h after hatching (hae); management of first feeding is short (24 h). During this phase the maximum mouth opening is estimated at 20-25% of total length (5 to 6 mm); there is a short larval period (7 days); and like other bryconids, Brycon sinuensis shows strong cannibalism at the beginning of the exogenous feeding [2,[4][5][6][7][8]. This behavior causes low survival rates and heterogeneity in larval size [2,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and interspecific hybrids are reared similarly. Larvae are fed Artemia nauplii during the first 7–10 days until they develop skin pigmentation 122,123 . Feeding ratios consist of 500 Artemia nauplii per larva per day during the first 5 days, and 1000 nauplii per larva per day from day 6 to 10, divided into 6 to 10 rations distributed along 24 h 26,122 .…”
Section: Rearing Practices For Early Life Stagesmentioning
confidence: 99%
“…After this initial period when body pigmentation is developed, larvae can be reared indistinctly in tanks connected to a recirculating system or in outdoor fertilised ponds, a choice that depends on available facilities (Table 5). 26,122,123 …”
Section: Rearing Practices For Early Life Stagesmentioning
confidence: 99%